ANTICONVULSANT ACTIVITY OF RAUWOLFIA TETRAPHYLLA LEAF EXTRACT IN SWISS ALBINO MICE - Singh, Aaditya; TRIPATHI, SHALINI; PN, SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Rauvolfia tetraphylla is a plant potentially applicable in Ayurvedic and Unani System of Medicine for the treatment of various diseases. However, the anticonvulsant activity of this plant has not been reported and studied. Therefore, the ethanolic extract of leaf from the plant R. tetraphylla is used to evaluate anticonvulsant activity. Methods: Anticonvulsant activity was screened using maximal electroshock seizure (MES) model and pentylenetetrazole (PTZ)-induced seizure model in Swiss albino mice. The ethanolic extract was also evaluated for rutin and gallic acid content by high-performance thin-layer chromatography studies. Results: Rutin and gallic acid contents were found as 15.60% and 7.81%, respectively. Ethanolic leaf extract (100–800 mg/kg) significantly reduced the duration of seizures which was induced by MES. The same doses also protected animals from PTZ-induced tonic seizures. Conclusion: The study demonstrates that R. tetraphylla plant leaves have significant anticonvulsant activity.